Strategi Dakwah Kelompok Milineal di Kota Kediri (Studi Kasus Kelompok Kajian Saff) - Taufik Alamin (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2020)
Da'wah is part of the Islamic teaching movement. This movement can be carried out in various ways, as long as it is in accordance with the principles of Islamic teachings. One of the interesting dakwah strategy models in this study is the Shaff study community in Kediri. This study community is an association that provides space for millennials to be able to learn to deepen Islamic science. As for the purpose of this research is to find out how the da'wah strategy carried out by the Shaff Study group to youth in the City of Kediri and to determine the factors that are supporting and inhibiting the Shaff Study group in preaching. The results of this study indicate that the Shaff study is in the practice of preaching to the millennial generation as facilitator of event organizer and collaborating with outsiders. This activity is conceptualized with a youthful nuance, namely by using the sharring method or casually asking and answering questions and the language used by da'i is also contemporary slang. The style of dress used by the cleric also adapts to the conditions of today's youth. Even so, there are a number of factors that become supporters and obstacles.